2012
DOI: 10.1111/j.1600-0587.2011.07227.x
|View full text |Cite
|
Sign up to set email alerts
|

Not‐so‐splendid isolation: modeling climate‐mediated range collapse of a montane mammalOchotonaprinceps across numerous ecoregions

Abstract: We modeled current and future distribution of suitable habitat for the talus-obligate montane mammal Ochotona princeps (American pika) across the western USA under increases in temperature associated with contemporary climate change, to: a) compare forecasts using only climate variables vs using those plus habitat considerations; b) identify possible patterns of range collapse (center vs margins, and large-vs small-sized patches); and c) compare conservation and management implications of changes at two taxono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
60
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 58 publications
0
60
3
Order By: Relevance
“…Additionally, aspects of vegetation cover have also been shown to correlate with pika distribution and indices of pika abundance (e.g., [43,44,45,46]). Suitable habitat in the southern portion of the species’ range has been repeatedly forecasted to be largely eliminated under future climate conditions [47,48,49]. However, research in locations with physically complex habitats that provide climatic microrefugia (e.g., low-elevation lava flows and moss-covered, heavily forested gorges), has shown that the species’ status and trend in such habitats are more robust than expected, considering the region’s macroclimate [50,51,52,53,54].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, aspects of vegetation cover have also been shown to correlate with pika distribution and indices of pika abundance (e.g., [43,44,45,46]). Suitable habitat in the southern portion of the species’ range has been repeatedly forecasted to be largely eliminated under future climate conditions [47,48,49]. However, research in locations with physically complex habitats that provide climatic microrefugia (e.g., low-elevation lava flows and moss-covered, heavily forested gorges), has shown that the species’ status and trend in such habitats are more robust than expected, considering the region’s macroclimate [50,51,52,53,54].…”
Section: Introductionmentioning
confidence: 99%
“…princeps at the species’ leading, northern (range) edge, where cold stress and persistent snowpack may play increased roles in limiting distribution, such that north-facing slopes and the highest elevations may have lower pika abundance. If a shifting climate is indeed driving extirpations of American pika populations in parts of the species’ range, the northern Rocky Mountains may be one of the species’ final refugia in the U.S. ([47,48], but see [54] for microrefugia-driven persistence in complex microhabitats). Additionally, very few studies have examined pika abundance across a large network of sites (i.e., [43,45,56,59,60] each of which involved <100 sites), and those with relatively large sample sizes span entire eco-regions and only examine occupancy (e.g., [61]), not abundance.…”
Section: Introductionmentioning
confidence: 99%
“…Pikas have also emerged as an important study species for investigating extinction risk in the face of rapidly changing climates [5,7,12-15]. Unlike the majority of woodland montane fauna whose continuous habitat allows for cross-valley dispersal among mountain ranges, pikas reliance on high-elevation talus habitat precludes their ability for dispersal to cooler latitudes [9].…”
Section: Introductionmentioning
confidence: 99%
“…We aimed to analyse faecal pellets using metabarcoding to identify the plants in the diet of the Royle's pika and examine the effects of talus characteristics, topography and plant richness; abundance; and seasonal dynamics (pre‐ and postmonsoon) on diet, across five sites in the western Himalaya, India. Food availability (plant species’ presence and abundance; Huntly, Smith, & Ivins, ; Dearing, , ; Wilkening et al., ; Bhattacharyya et al., , 2014a; Bhattacharyya & Ray, ), habitat topography (elevation, slope, aspect; Walker, Halfpenny, Walker, & Wessman, ; Deems, Birkeland, & Hansen, ; Wilkening et al., ; Rodhouse et al., ; Gurung et al., ) and predation risk (rock cover, crevice depth, distance to the nearest area of talus; Calkins, Beever, Boykin, Frey, & Andersen, ; Bhattacharyya et al., ,b; Castillo, Epps, Davis, & Cushman, ; Bhattacharyya et al., ) significantly impact the foraging ecology of the Royle's pika and potentially influence access to nutritive plants, and thereby affect individual fitness (Bhattacharyya, ). For talus‐dwelling Ochotona spp., talus size (area) and connectivity between talus are known to influence the habitat occupancy (Franken & Hik, ).…”
Section: Introductionmentioning
confidence: 99%